Elevated Lipoprotein-Associated Phospholipase A2 Is Associated With Intracranial Atherosclerosis - Wang, Yuan; Liu, Gang; Song, Haiqing; Cao, Catherine; Ji, Xunming; Cao, Guodong (Frontiers in Neurology, 2022)
Background: Lipoprotein-associated phospholipase A2 (Lp-PLA2) is an inflammatory factor in atherosclerotic plaque pathogenesis and is associated with an increased risk of ischemic stroke. Whether Lp-PLA2 is associated with stenosis subtypes in acute ischemic stroke (AIS) has not been investigated. Methods: 126 eligible AIS patients were divided into four groups 1) no cerebral artery stenosis (NCS); 2) intracranial artery stenosis (ICAS); 3) extracranial artery stenosis (ECAS); and 4) combined intracranial and extracranial artery stenosis (IECS). The associations between serum Lp-PLA2 levels and the stenosis subtypes were assessed. Results: The ICAS group had a lower frequency of dyslipidemia as compared with the NCS group and the IECS group (35.3% vs. 70% vs. 71.8%, respectively; P=0.001), and was more likely to be symptomatic than the ECAS group (76.5% vs. 43.8%, respectively; P=0.014). Lp-PLA2 levels in the ICAS group were 112.2±66.8 μg/L, higher than in the NCS, ECAS, and IECS groups (81.7±38.5, 106.1±57.8, 89.3±52.2 μg/L, respectively, P=0.025). In the 3rd and 4th quartiles of Lp-PLA2 levels, stenosis had occurred more frequently in the ICAS group than in the other three groups (3rd Q: 50.0% vs. 3.1% vs. 28.1% vs. 18.8%, P=0.002; 4th Q: 48.4% vs. 16.1% vs. 25.8% vs. 9.7%, P=0.014). Lp-PLA2 levels were higher in patients with more or severe stenosis in the ICAS group. Conclusions: Elevated Lp-PLA2 levels were differentially associated with increased risk of incidence in AIS patients with ICAS compared to those with ECAS or no stenosis. Lp-PLA2 may be a promising biomarker and potential therapeutic target for ICAS.